Experimental Approaches to Neutrino Nuclear Responses for ββ Decays and Astro-Neutrinos - Ejiri, Hiroyasu (Frontiers in Physics, 2021)
Fundamental properties of neutrinos are investigated by studying double beta decays (DBDs), while astro-neutrino nucleo-syntheses and astro-neutrino productions are investigated by studying inverse beta decays (IBDs) induced by astro-neutrinos. Neutrino nuclear responses for DBDs and IBDs are crucial for these neutrino studies in nuclei. This reports briefly perspectives on experimental studies of neutrino nuclear responses (square of nuclear matrix element) for DBDs and astro-neutrinos by using nuclear and leptonic (muon) charge exchange reactions.